Use of the Bipartite System in Industrial Relations - Rika Jamin Marbun (Budapest International Research and Critics University, 2021)
Basically, industrial relations between workers / workers and employers can not always be established harmoniously. At any time, there could be a dispute between the parties. This dispute is triggered by differences in interests between workers and employers. So, disputes are inevitable. But this industrial relations dispute cannot be left alone. It must be resolved immediately by the disputing parties. Otherwise, it will result in disruption of the production process of goods and services in the company which in turn will disrupt economic stability. The provisions of Law No. 2 of 2004 on Industrial Relations Dispute Resolution have provided the appropriate mechanism to resolve any disputes in industrial relations. One of the preferred mechanisms in this case is bipartite. This mechanism is a mechanism that is taken outside the court path (non litigation). Bipartite in its implementation is mandatory. Therefore, in every industrial relations dispute must first be pursued bipartite mechanism in the settlement. This bipartite priority gives authority to the disputing parties to be able to discuss, discuss and find solutions to the disputes at hand. The direct involvement of the parties is expected to provide a settlement that benefits both parties. This is very appropriate because the parties are more aware of their respective wills / desires even better understand how to sit disputes that occur.